Entrepreneurship as a Neglected Pitfall in Future Finnish Teachers' Readiness to Teach 21st Century Competencies and Financial Literacy: Expectancies, Values, and Capability - Mette Ranta; Milla Kruskopf; Marilla Kortesalmi; Panu Kalmi; Kirsti Lonka (MDPI AG, 2022)
The aim of this study was to examine entrepreneurship in the context of future Finnish teachers' readiness to teach 21st century (broad-based) competencies. Teachers' self-efficacy in teaching entrepreneurial skills and financial matters is vital for their pupils to actively participate and flourish in future society. The study utilized survey data of future teachers' expectancy-values in teaching seven broad-based competencies of the current national curriculum and their financial literacy. Future teachers expressed high interest in all competencies but reported the least self-efficacy and highest cost in teaching ICT as well as working life and entrepreneurship competencies. Teaching self-efficacy (TSE) in entrepreneurial competencies was predicted by subjective evaluations of financial capability and TSE in consumer skills. Teaching STEM subjects as well as male gender were related to better objective financial knowledge. We discuss the implications of observed financial capability, lack in self-efficacy, and high experienced cost of teaching these competencies. Support for future teachers' readiness to teach working life skills, entrepreneurship, and financial literacy through phenomenon-based school subject collaboration, formal teacher training, and digital applications are emphasized.